Extracellular vesicles derived from human dental mesenchymal stem cells stimulated with low-intensity pulsed ultrasound alleviate inflammation-induced bone loss in a mouse model of periodontitis - Tingwei Zhang; Ziqi Chen; Mengyuan Zhu; Xuan Jing; Xiaohui Xu; Xulei Yuan; Mengjiao Zhou; Yanan Zhang; Miao Lu; Duanjing Chen; Shihan Xu; Jinlin Song (Genes and Diseases, 2023)
Extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) have emerged as a new mode of intercellular crosstalk and are responsible for many of the therapeutic effects of MSCs. To promote the application of MSC-EVs, recent studies have focused on the manipulation of MSCs to improve the production of EVs and EV-mediated activities. The current paper details an optimization method using non-invasive low-intensity pulsed ultrasound (LIPUS) as the stimulation for improving oral MSC-EV production and effectiveness. Stem cells from apical papilla (SCAP), a type of oral mesenchymal stem cell, displayed intensity-dependent pro-osteogenic and anti-inflammatory responses to LIPUS without significant cytotoxicity or apoptosis. The stimuli increased the secretion of EVs by promoting the expression of neutral sphingomyelinases in SCAP. In addition, EVs from LIPUS-induced SCAP exhibited stronger efficacy in promoting the osteogenic differentiation and anti-inflammation of periodontal ligament cells in vitro and alleviating oral inflammatory bone loss in vivo. In addition, LIPUS stimulation affected the physical characteristics and miRNA cargo of SCAP-EVs. Further investigations indicated that miR-935 is an important mediator of the pro-osteogenic and anti-inflammatory capabilities of LIPUS-induced SCAP-EVs. Taken together, these findings demonstrate that LIPUS is a simple and effective physical method to optimize SCAP-EV production and efficacy.